Implementation of a fully virtual enterprise-wide clinical evidence-based suicide prevention program in the U. S. Department of Veterans Affairs: the suicide prevention 2.0 clinical telehealth initiative - Landes, Sara J.; Walker, Jessica A.; Bekman, Nicole M.; Kumpula, Mandy J.; Lhermitte, Samantha L.; Hoff, Rani A.; van Engelen, Lisanne M.; Betthauser, Lisa M.; Beaudreau, Sherry A.; Batdorf, Wendy H.; Kearney, Lisa K.; Miller, Matthew A.; et al. (Frontiers in Psychiatry, 2026)
IntroductionVeteran death by suicide is a complex issue made up of many factors. Despite the high need for mental health treatment, and treatments that specifically target suicide, evidence-based psychotherapies (EBPs) are difficult to access, even more so in rural areas. In concordance with the 2018 National Strategy for Preventing Veteran Suicide, VA suicide prevention leadership developed Suicide Prevention 2.0 (SP 2.0) to implement a public health model that includes community-based prevention strategies and improves clinical interventions within VA. The Suicide Prevention 2.0 Clinical Telehealth program was implemented in each of VA’s 18 regional Clinical Resource Hubs and expanded clinical intervention strategies within VA by implementing four EBPs for Suicide Prevention (EBP-SP) via telehealth: the Safety Planning Intervention, Problem-Solving Therapy for Suicide Prevention, Cognitive Behavioral Therapy for Suicide Prevention, and Dialectical Behavior Therapy.MethodsA wide variety of implementation strategies were used (e.g., access new funding, training, consultation, create new clinical teams). The primary inclusion criterion for veteran referral to SP 2.0 Clinical Telehealth is a recent history of suicidal self-directed violence. Implementation was guided by the Exploration, Preparation, Implementation, and Sustainment (EPIS) framework and RE-AIM was used as an evaluation framework.ResultsBy April 2023, SP 2.0 Clinical Telehealth services were available in all 18 regions and in 139 of 139 (100%) VA health care systems in the U.S. By the end of September 2024, the program had hired 137 therapists and retained 78.10% in their role, and 100% were trained in two or more EBP-SPs. By the end of September 2024, the program received 23,628 referrals nationwide. Increasing referral rates year over year suggests ongoing sustained reach.DiscussionSP 2.0 Clinical Telehealth represents the first and only enterprise-wide fully virtual evidence-based treatment program for veterans with a recent history of suicidal self-directed violence. The program’s implementation was successful in reaching all VISNs and all VA health care systems in the U.S. The SP 2.0 Clinical Telehealth program can be used as a model for other large health care systems looking to improve provision of evidence-based interventions for suicide prevention.